River-influenced beluga (Delphinapterus leucas) summer habitat use in western Hudson Bay, Canada - Emma L. Ausen; David G. Barber; Atreya Basu; Jens Ehn; David Walker; Laura Dalman; Marianne Marcoux (Arctic Science, 2023)
River estuaries along western Hudson Bay, Canada, are important summer habitats for beluga whales (Delphinapterus leucus (Pallas, 1776)) and subject to increasing industrial development activities including vessel traffic. The feasibility of establishing a National Marine Conservation Area (NMCA) in western Hudson Bay is under consideration, requiring baseline studies and habitat monitoring. In this study, beluga whale locations were identified using aerial photographs collected during summer 2018 of the Seal, Knife, Churchill, and Nelson River estuaries. Sentinel 2 wavelength bands were used to outline river plume boundaries for the Seal, Knife, and Churchill Rivers. Multiple discriminant analysis was used to differentiate between beluga habitat areas according to their environmental characteristics including concentration of total suspended sediments (TSS), and coloured dissolved organic matter (CDOM). The Seal River estuary, Knife River estuary, Churchill River outer estuary, Churchill River estuary, and Nelson River estuary were identified as distinct habitat areas. Resource selection functions and model selection were used to determine that habitat variables related to prey availability were important for beluga habitat selection, including TSS, CDOM, and the distance to river mouth or river plume. Identification of preferred habitat and habitat areas in this study are imperative for future management decisions including establishment of an NMCA.